Simulation and analysis of Si deposition in turbulent CVD reactors - 魏家星 徐睿 禹燕飞 侯金亮 李昌烽 (Journal of semiconductors, 2014)
Numerical simulation, based on simple reaction models that manifest the deposition quality of silicon from silane, was undertaken to investigate the horizontal reactor, with longitudinal and transversal aspect ratios of 10 and 4, respectively. The effects of Rayleigh （Ra） and Reynolds （Re） numbers on the Si deposition rate in these turbulent-type reactors are discussed. The results show that the time-averaged deposition rate is fairly uniform and fast, although the instantaneous deposition is non-uniform in these turbulent reactors. In addition, the increase of the Re number within a certain range can compensate for the path loss of the reactant and obviously enhance the downstream deposition rate, but deteriorate the transverse distribution of the deposition.